Volatile profiling of alcoholic food and beverages and industrial alcohol using GCxGC-ToF-MS for halal authentication - K., Farah Azura; Mat Hashim, Dzulkifly; Che Man, Yaakob; Sazili, Awis Qurni (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
This study focuses on the identification of the origins of alcohol present in foods using comprehensive two-dimensional Gas Chromatography Time of Flight Mass Spectrometry (GCxGC-ToF-MS). The volatile profiles of alcohols from industrial samples and alcoholic food were extracted by Solid Phase Microextraction (SPME) and analysed using GCxGC-ToF-MS.For this study, different types of wines including red, white and cooking wines, and an industrial alcohol sample from sugarcane molasses were tested. The classification of volatile compounds based on the organized structure of the peaks in the GCxGC contour plot has enabled alcohols from different origins to be effectively characterized. Evaluation of the data by Principal Component Analysis (PCA) revealed that the variables ethyl alcohol, 1-Propanol, 1-Butanol 3-methyl are able to distinguish between these alcohols. It can thus be observed that chromatographic metabolomic profiling represent a valuable approach in identifying the origin of alcohols present in foods and beverage.